IVIG response in pediatric acute-onset neuropsychiatric syndrome correlates with reduction in pro-inflammatory monocytes and neuropsychiatric measures - Melamed, Isaac; Rahman, Shamma; Pein, Heather; Heffron, Melinda; Frankovich, Jennifer; Kreuwel, Huub; Mellins, Elizabeth D. (Frontiers in Immunology, 2024)
Introduction Pediatric Acute-Onset Neuropsychiatric Syndrome (PANS) is characterized by abrupt onset of obsessive-compulsive disorder or eating restriction along with the abrupt onset of other co-occurring symptoms (tics, behavioral and cognitive regression, etc.). PANS is thought to be a post-infectious immunopsychiatric disorder, although as with most post-infectious disorders, it is challenging to establish a causal relationship with proposed infectious triggers. Intravenous immunoglobulin (IVIG) can modulate inflammation and support the elimination of infection and has been used for treatment of many post-infectious inflammatory disorders and autoimmune conditions. The aim of the study is to explore the pro-inflammatory state in PANS before and after administration of IVIG. Methods Children with moderate-to-severe PANS received six infusions of IVIG (Octagam 5%, Octapharma) every 3 weeks with post treatment follow-up. Blood samples and psychiatric measures were obtained at Visits 1 (pre-treatment), 7 and 8 (4 and 11 weeks after last infusion, respectively). Myeloid cell activation was assessed via flow cytometry. Results All ten patients included in the study were male, White, with mean age 12.4 years (range 6–16). Statistically significant improvements following IVIG treatment were demonstrated in all psychometric assessments and parent questionnaires including CY-BOCS (obsessive compulsive scale), YGTSS (tic scale) and a parent PANS rating scale (for all scales p<0.001). The fraction of pro-inflammatory monocytes and dendritic cells decreased from pre-IVIG treatment levels. The proportional reductions were not compensated by increases in total white blood cells; pro-inflammatory monocytes post-IVIG were decreased as a proportion of CD14+ myeloid cells and in absolute number. Conclusions The results of this study suggest that active PANS is associated with a pro-inflammatory state. This pro-inflammatory profile and psychometric scores improved following IVIG treatment. Future work will aim to further elucidate the roles of innate and adaptive immune responses in PANS and the regulatory mechanism(s) of IVIG in PANS treatment.